(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The aim of this article is to analyze the memories produced about the disappeared and their militancy practices based on the uses and resignifications of the episode known as la noche de los lápices. We will focus on the practices and public discourses produced on September 16, between 1986 and 1996, especially the participation of secondary students in these memorial processes. We can observe that during those years the remembrance of the episode in question has been an axis around which the secondary students at different junctures during democracy produced their senses about state violence during the last dictatorship and about the disappeared. In this process, they also produced a genealogy of struggle for the defense of education and for the political par- ticipation of young people in the present.